Physicochemical, antioxidant and starch-digesting enzymes inhibitory properties of pearl millet and sweet detar gluten-free flour blends, and sensory qualities of their breads - Irondi, Emmanuel Anyachukwu; Imam, Yunus Temitayo; Ajani, Emmanuel Oladipo (Frontiers in Food Science and Technology, 2022)
Natural sources of hydrocolloids may serve as healthier alternatives to modified hydrocolloids as gluten replacement in gluten-free food products. In this study, the physicochemical, antioxidant and starch-digesting enzymes inhibitory properties of gluten-free whole pearl millet flour (PMF) blended with 1.5% and 3% of either sweet detar flour (SDF, a natural source of hydrocolloids) or sodium carboxymethyl cellulose (SCMC, a modified hydrocolloid), and the sensory qualities of their breads were evaluated. White wheat flour (WWF) and its bread served as the control flour and bread, respectively. Amylose level and solubility index of the blends decreased, whereas their water absorption capacity, peak and final viscosity increased significantly as their proportions of SDF and SCMC increased. Total phenolics, tannins, and total flavonoids contents; DPPH•, ABTS•+ scavenging capacity, and reducing power; α-amylase and α-glucosidase inhibitory activities were significantly higher in PMF and its blends with SDF and SCMC than in the WWF. Further, the blend of PMF and 1.5% SDF had a stronger α-amylase and α-glucosidase inhibitory activity than those of PMF and SCMC (1.5 and 3%). Although the sensory qualities of the WWF bread were better than those of PMF and its blends with SDF and SCMC, the sensory qualities of PMF-SDF and PMF-SCMC breads were comparable. The study indicates that SDF could be a good substitute for SCMC in the development of PMF-based gluten-free bread, with an enhanced starch-digesting enzymes inhibitory property, targeting celiac disease and type 2 diabetes patients.